Beyond Formal Legality: A Maqashid al-Shari'ah Approach to Ethical Legitimacy in Electronic Consent across Notarial, Healthcare, and Child Protection Practices - Anis Mashdurohatun; Naimah; Raendhi Rahmadi; Ismayana; Hari Suparjo (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
The rapid expansion of digital technology has transformed consent practices across various sectors, including notarial services, healthcare, and child protection. While electronic consent mechanisms are increasingly recognized as legally valid, concerns remain regarding their ability to ensure meaningful autonomy, informed understanding, and protection of vulnerable individuals. This study aims to examine the ethical limitations of contemporary electronic consent regimes and to evaluate them through the normative framework of maqashid al-shari‘ah. Employing doctrinal and comparative legal research, the study analyzes Indonesian digital legal regulations alongside selected international frameworks, including the General Data Protection Regulation (GDPR), the Children’s Online Privacy Protection Act (COPPA), and the United Kingdom’s Age Appropriate Design Code. The findings reveal that legally valid electronic consent often functions as procedural authorization rather than substantive ethical consent. In notarial services, consent mechanisms primarily verify identity without adequately ensuring voluntariness; in healthcare, digital consent may fail to secure meaningful patient comprehension; and in child protection, click-based consent frequently overlooks the limited capacity and vulnerability of minors. These findings indicate a persistent gap between legal validity and ethical legitimacy in digital governance. The study concludes that maqashid al-shari‘ah provides a human-centered framework that reorients electronic consent from procedural compliance toward the protection of autonomy, dignity, welfare, and vulnerable users in digitally mediated environments.